Fire Hazards of Coal Storage Sites - Monitoring and Protection - Słota, Zbigniew; Słota, Krzysztof; Morcinek-Słota, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Coal`s high propensity for spontaneous combustion can be the cause of fires in coal heaps located at mine sites, power plants, distribution or coal handling points. The application of appropriate measures to prevent coal from self-igniting and consequently to protect against fire.
Keywords: coal storage sites; fire hazards; monitoring; składowiska węgla; zagrożenia pożarowe; monitorowanie